Automatic dependent surveillance‐broadcast time delay estimation based on extended recursive maximum correntropy algorithm. Issue 8 (1st October 2016) - Luan, Shengyang; Qiu, Tianshuang; Song, Aimin; Wang, Peng; Li, Jingchun; Tan, Haifeng
Abstract : In this study, a novel adaptive algorithm, termed extended recursive maximum correntropy (EX‐RMC), is proposed to estimate the time delay of automatic dependent surveillance‐broadcast (ADS‐B), an up‐to‐date surveillance technology in civil aviation. The proposed algorithm is designed to deal with both the random time‐varying delay and the impulsive noise. The superiority of EX‐RMC in tracking time‐varying state of an unknown plant has been verified by simulation experiments. On‐site experiments are also carried out to demonstrate the practical value of the ADS‐B time delay estimation method based on EX‐RMC.